Description of the adult male, larva and pupa of Topomyia (Topomyia) aureoventer (Diptera: Culicidae) in India - Natarajan, R.; Eapen, Alex; Jambulingam, P. (Zootaxa, 2019)
The original description of Topomyia aureoventer by Theobald (1910) included only the adult female. Description of the adult male, pupa and larva, with figures of the male genitalia, pupa and larva, are provided. The larva is predacious with well-developed mandibles and inhabits leaf axils of Colocasia plants.